2017
DOI: 10.1016/j.biopsych.2017.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Cell- and Single Molecule-Based Methods to Detect Anti- N -Methyl-D-Aspartate Receptor Autoantibodies in Patients With First-Episode Psychosis From the OPTiMiSE Project

Abstract: Circulating autoantibodies against glutamatergic N-methyl-D-aspartate receptor (NMDAR) have been reported in a proportion of patients with psychotic disorders, raising hopes for more appropriate treatment for these antibody-positive patients. However, the prevalence of circulating autoantibodies against glutamatergic NMDAR in psychotic disorders remains controversial, with detection prevalence rates and immunoglobulin classes varying considerably between studies, perhaps because of different detection methods.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
65
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 24 publications
(20 reference statements)
3
65
0
1
Order By: Relevance
“…Possible contributory factors include the lack of a control group in many studies, variability in terms of diagnosis and illness chronicity (frequently not reported in detail), and differences among studies with respect to how antibodies were tested, making interpretation of the results difficult, particularly given that there is ongoing debate about the most sensitive and specific methods for antibody detection. Regarding the latter point, the most frequently used method in the reviewed studies (the commercially available fixed CBA) is believed to have high specificity but lower sensitivity [14, 41]. Considering this, it is curious that those studies that found seropositivity in both patients and controls tended to use the commercial CBA, whereas those that only found seropositivity in patients used live CBAs.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Possible contributory factors include the lack of a control group in many studies, variability in terms of diagnosis and illness chronicity (frequently not reported in detail), and differences among studies with respect to how antibodies were tested, making interpretation of the results difficult, particularly given that there is ongoing debate about the most sensitive and specific methods for antibody detection. Regarding the latter point, the most frequently used method in the reviewed studies (the commercially available fixed CBA) is believed to have high specificity but lower sensitivity [14, 41]. Considering this, it is curious that those studies that found seropositivity in both patients and controls tended to use the commercial CBA, whereas those that only found seropositivity in patients used live CBAs.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, given the available information, diagnostic differences between samples do not appear to be responsible. For instance, although the vast majority of negative studies included patients with DSM IV, DSM IV-TR, DSM 5, or ICD-10 schizophrenia diagnoses, among numerous other diagnoses, so too did most of the positive studies [10-12, 14, 16], and two of these studies explicitly reported finding antibody positivity in patients with a diagnosis of schizophrenia [10, 14]. Additionally, although the other two positive studies did not report antibody positivity results according to diagnosis, they only included patients with schizophrenia and schizoaffective disorder [11, 12].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations